Lessons from the Discovery of Mitochondrial Fragmentation (Fission): A Review and Update - Dmitry B. Zorov; Ivan A. Vorobjev; Vasily A. Popkov; Valentina A. Babenko; Ljubava D. Zorova; Irina B. Pevzner; Denis N. Silachev; Savva D. Zorov; Nadezda V. Andrianova; Egor Y. Plotnikov (Cells, 2019)
Thirty-five years ago, we described fragmentation of the mitochondrial population in a living cell into small vesicles (mitochondrial fission). Subsequently, this phenomenon has become an object of general interest due to its involvement in the process of oxidative stress-related cell death and having high relevance to the incidence of a pathological phenotype. Tentatively, the key component of mitochondrial fission process is segregation and further asymmetric separation of a mitochondrial body yielding healthy (normally functioning) and impaired (incapable to function in a normal way) organelles with subsequent decomposition and removal of impaired elements through autophagy (mitophagy). We speculate that mitochondria contain cytoskeletal elements, which maintain the mitochondrial shape, and also are involved in the process of intramitochondrial segregation of waste products. We suggest that perturbation of the mitochondrial fission/fusion machinery and slowdown of the removal process of nonfunctional mitochondrial structures led to the increase of the proportion of impaired mitochondrial elements. When the concentration of malfunctioning mitochondria reaches a certain threshold, this can lead to various pathologies, including aging. Overall, we suggest a process of mitochondrial fission to be an essential component of a complex system controlling a healthy cell phenotype. The role of reactive oxygen species in mitochondrial fission is discussed.